Perceived similarity and acculturation attitudes of native and inmigrants (2012)
The aim of the work is to evaluate if there are differences in similarity perceived depending on the acculturation option of natives and immigrant. It will also be taken into account the Relative Acculturation Extended Model (RAEM) socio - cultural domains (public and private). This study involved two samples of Spaniards (499 Spaniards rating Romanians group, and 493 Spaniards rating Ecuadorians group) selected by polietapic sampling. The minority group comprised 500 Romanians and 475 Ecuadorians selected by incidental sampling. All participants, Spaniards and immigrants, were residents in 12 municipalities in four autonomous regions in the Mediterranean (Spain) with h igh rates of immigration. All the samples completed a questionnaire with RAEM acculturation indicators (both public and private domains). They completed a perceived similarity test as well. The results show differences in acculturation -preferred options for both public and private domains in all the samples. In the same way, differences between perceived similarities of the samples, depending on the attitudes of acculturation, were found. In future research it should be attended also to variables as the group identification as moderating of the intergroup processes.